Don't wake me at Doyles the remarkable memoir of an ordinary Irish woman and her extraordinary life - Murphy, Maura 1928-
When seventy-year-old Maura Murphy discovered she had cancer, she left her husband of fifty years and started writing her memoirs. Born 'chronically ugly and as cross as a briar' into a poor rural homestead in 1920s Ireland, Maura lived much of her adult life in England, where she raised nine children and fought to keep together a family ravaged by poverty and alcohol. The voice of a silent generation of an immigrant-Irish underclass, Maura Murphy's tough and remarkable life is a compellingly written account of struggle and survival like no other. With all the immediacy and impact of Frank McCourt's prize-winning ANGELA'S ASHES, Maura's voice is feisty, funny and fearless. And she needed to be all those things to survive an extraordinary series of privations and abuses. Her story is compelling and upbeat despite everything.